MAKING A CASE (Fiep Bulletin - online, 2014)
This article presents and discusses research evidence in support of the importance of physical activity for people of all ages. Studies over the last 20-30 years have shown the benefits of physical activity in preventing cardiovascular diseases, diabetes, colon and breast cancer, and osteoporosis. It has been found that an active life contributes to improve health conditions and reduce obesity in children and adolescents, and has a direct effect in their later years. Important mental health benefits such as depression and stress reduction have been reported. Research still being conducted suggests that physical activity may have a great impact on cognitive function, improving academic performance. Besides the benefits to one’s physical and mental health, physical activity is also considered to play a role in the development of social interaction skills through the practice of planned and controlled games and sports. Some authors have shown a positive relation between physical activity and delinquency reduction. A few studies have recently reported considerable savings in health care costs, as an active lifestyle may help to prevent diseases and protect seniors against institutionalization in the later years. It is important to be aware that physical activity is beneficial to people, young through the elderly, and that physical education programs in schools prepare children and adolescents to be healthy and develop good habits and attitudes throughout their lives.